Assessing the rate and reversibility of large‐herbivore effects on community composition in a semi‐arid grassland ecosystem. (13th September 2020) - Wilmer, Hailey; Augustine, David J.; Derner, Justin D.; Milchunas, Daniel G.
Abstract: Questions: What are the rate, reversibility, and degree of symmetry in plant species compositional change in response to the addition and removal of cattle grazing in the shortgrass steppe? Specifically, how does the imposition and removal of grazing affect the abundance of perennial C4 shortgrasses and C3 midgrasses that are of primary importance for livestock production in the region? Location: Shortgrass steppe, northeastern Colorado, USA, in the North American Great Plains. Methods: We evaluate rates and magnitude of basal cover change in newly ungrazed and newly grazed sites (established in 1991), relative to change in long‐term (grazed and ungrazed) comparison treatments (established in 1939) over 25 years. We also compare shifts in species basal cover in newly implemented treatments relative to baseline community composition measured at the start of the study. Results: Unlike the limited change observed in long‐term treatments between 1939 and 1991, we documented more rapid, reversible and largely symmetric effects of both the imposition and removal of grazing between 1992 and 2017. This was primarily due to differences in the rate of increase in basal cover of C3 midgrasses, litter, and bare ground. However, the rate and direction of change differed when assessed relative to continuously evaluated and (early‐treatment) baseline cover data. Conclusions: Studies of plant community change in response to large‐herbivore grazing under varying ecological conditions and management regimes are needed to effectively guide the development and revision of state‐and‐transition models (STMs) for grassland managers, and to better detect and plan for dynamic ecological conditions. Effective adaptive management and STM development under a changing climate will recognize that effects of grazing and removal of grazing on shortgrass steppe can be reversible in a relatively symmetrical pattern, occurring within 6–16 years. Abstract : We empiricaly evaluate of the effects of grazing on semi‐arid grassland hypothesized by State‐and‐Transition Models using a 25‐year grazing exclosure reversal experiment in the Great Plains, USA. We document reversible and largely symmetric effects of the imposition and removal of grazing between 1992 and 2017, which altered the relative abundance of C3 midgrasses vs. C4 shortgrass. Photo: Nick Dufek, ARS.